Prevalence, incidence, and outcomes of hepatitis E virus coinfection in patients with chronic hepatitis C - Jang, Eun Sun; Choi, Gwang Hyeon; Kim, Young Seok; Kim, In Hee; Lee, Youn Jae; Cho, Sung Beom; Kim, Yun-Tae; Jeong, Sook-Hyang (Scientific reports, 2023)
This study aimed to elucidate the anti-hepatitis E virus (HEV) immunoglobulin G (IgG) prevalence and incidence of seroconversion and seroreversion as well as its risk factors and to analyze the clinical outcomes of HEV and hepatitis C virus (HCV) coinfected patients compared to those of HCV-monoinfected patients. We prospectively enrolled 502 viremic HCV patients with paired plasma samples (at intervals of ≥ 12 months) from 5 tertiary hospitals. Anti-HEV IgG positivity was tested using the Wantai ELISA kit in all paired samples. Mean age was 58.2 ± 11.5 years old, 48.2% were male, 29.9% of patients had liver cirrhosis, and 9.4% of patients were diagnosed with hepatocellular carcinoma (HCC). The overall prevalence of anti-HEV IgG positivity at enrollment was 33.3%, with a higher prevalence in males and increasing prevalence according to the subject’s age. During the 916.4 person-year, the HEV incidence rate was 0.98/100 person-years (9/335, 2.7%). Hepatic decompensation or liver-related mortality was not observed. There were six seroreversion cases among 172 anti-HEV-positive patients (1.22/100 person-years). In conclusion, approximately one-third of the adult Korean chronic HCV patients were anti-HEV IgG positive. The HEV incidence rate was 1 in 100 persons per year, without adverse hepatic outcomes or mortality.